A design of CMOS tunable current amplifiers - Kaewdang, Khanittha; Surakampontom, Wanlop; Fujii, Nobuo (My University, 2004)
Two CMOS tunable current amplifiers are proposed in this paper. They are voltage-controlled current gain and current-controlled current gain. Both circuits are designed based on CMOS OTA which amplifiers are linearly tunable. The circuits achieve their linearity by squaring the nonlinear transconductance of the balanced CMOS OTA. The proposed voltage-controlled current amplifier can be linearly tuned by DC voltage. The amplifier's nonlinearity is less than 1% for the voltage control (Vc) range from -2V to 2V. The current-controlled current amplifier can also have a linearly-tunable current gain by DC bias current over three decades (0.1-20) with an error less than 1.5%. The performances of the proposed circuit are discussed and confirmed through PSPICE simulation.